The effect of dibutyryl cyclic adenosine-3'-5'-monophosphate on protein secretion from the rat exocrine pancreas in vitro. - Fast, D (1976)
1 The mechanism by which dibutyryl cyclic adenosine-3'-5'-monophosphate (dibutyryl cyclic AMP) potentiates the secretory effect of carbachol in rat exocrine pancreas was investigated. 2 Dibutyryl cyclic AMP potentiated the secretory effect of carbachol only at carbachol concentrations greater than or equal to 10(-7) mol/l; was independent of carbachol at concentrations greater than 10(-7) mol/l and was inversely proportional to extracellular [Ca2+]. 3 Carbachol increased and dibutyryl cyclic AMP reduced the rate of 45Ca efflux from the tissue. 4 A-23187 stimulated 3H-protein release in the presence of Ca2+ and this effect was potentiated by dibutyryl cyclic AMP; the degree of potentiation was inversely proportional to extracellular [Ca2+]. At 10(-3) mol/l [Ca2+] the potentiation occurred only at ionophore concentrations less than or equal to 10(-6) mol/litre. 5 These results support the hypothesis that dibutyryl cyclic AMP potentiates the effect of secretagogues in rat exocrine pancreas by maintaining an elevated intracellular calcium concentration. It does so by inhibiting Ca2+ efflux. The results also suggest that the limiting factor in carbachol-stimulated secretion, at all concentrations of carbachol, is intracellular [Ca2+].